Soil properties and computed tomography scans (CT-scans) of two thermo-erosion gullies and the adjacent tundra polygons on Bylot Island, Nunavut, Canada ... : Propriétés des sols et données de tomodensitométrie (CT-scans) de deux ravins de thermo-érosion et des polygones de toundra adjacents sur l'île Bylot, Nunavut, Canada ... - Fortier, Daniel; Gagnon, Samuel; Veillette, Audrey; Godin, Étienne (Nordicana D, 2024)
This dataset presents data on soil properties (volumetric ice content, organic matter content, grain size) that come from two thermo-erosion gullies that were studied in the Sirmilik National Park on Bylot Island, NU, Canada. The first gully, TEG1, formed in 1999 and is still active today (2024). Nine boreholes were drilled at TEG1 in June 2013 in three subsites at the following locations: one borehole on an undisturbed polygon in the periphery of the gully, one borehole on a drained polygon near the edge of the gully, and one borehole in the slope of the gully. The second gully, TEG2, is a gully that has been stabilized for at least 66 years. Eight boreholes were drilled at TEG2 in July 2016 at the following locations: two boreholes on undisturbed polygons in the periphery of the gully, two boreholes on drained polygons near the edge of the gully, three boreholes in the slope of the gully and one borehole at the bottom of the gully channel. All cores were scanned by tomodensitometry (CT scan) at the Centre ... : Ces données sur les propriétés des sols (teneur en glace volumétrique, teneur en matière organique, granulométrie) proviennent de deux ravins de thermo-érosion qui ont été étudiés dans le parc national Sirmilik sur l'île Bylot, NU, Canada. Le premier ravin, TEG1, est un ravin qui s'est formé en 1999 et qui est toujours actif à ce jour (2024). Neuf forages ont été faits à TEG1 en juin 2013 dans trois sous-sites aux emplacements suivants: un forage sur un polygone intact en périphérie du ravin, un forage sur un polygone drainé près de la bordure du ravin et un forage dans la pente du ravin. Le deuxième ravin, TEG2, est un ravin qui est stabilisé depuis au moins 66 ans. Huit forages ont été faits à TEG2 en juillet 2016 aux emplacements suivants: deux forages sur des polygones intacts en périphérie du ravin, deux forages sur des polygones drainés près de la bordure du ravin, trois forages dans les pentes du ravin et un forage dans le chenal du ravin. Toutes les carottes ont été numérisées par tomodensitométrie ...